Efficient synthesis of tert-butyl 3-cyano-3-cyclopropyl-2-oxopyrrolidine-4-carboxylates: Highly functionalized 2-pyrrolidinone enabling access to novel macrocyclic Tyk2 inhibitors. Issue 5 (1st March 2020) - Sasaki, Yusuke; Tokuhara, Hidekazu; Ohba, Yusuke; Okabe, Atsutoshi; Nakayama, Masaharu; Nakagawa, Hideyuki; Skene, Robert; Hoffman, Isaac; Zou, Hua; Yoshida, Masato
Graphical abstract: Abstract: Herein we report an efficient method for the synthesis of a highly functionalized 2-pyrrolidinone, tert -butyl 3-cyano-3-cyclopropyl-2-oxopyrrolidine-4-carboxylate, from readily available starting materials. Utility of this compound was demonstrated in the synthesis of a novel series of macrocyclic Tyk2 inhibitors, leading to the identification of a potent and selective macrocyclic Tyk2 inhibitor (26 ).